PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS APLIKASI CANVA PADA MATERI CIRI-CIRI BANGUN DATAR SEGI EMPAT DI KELAS IV SEKOLAH DASAR - Senyo, Farhan; Masniladevi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the limited use of engaging, interactive, and easily understandable learning media in mathematics instruction. It aims to examine the validity and practicality of Android-based learning media designed using the Canva application. The problems identified in this study were obtained from observations and needs analysis conducted in several elementary schools, which revealed that teachers rarely utilize technology-based learning media in the teaching process. This research employs a Research and Development (R&D) method using the ADDIE model, which consists of five systematic stages: Analyze, Design, Development, Implementation, and Evaluation. The data collected in this study include validation data and practicality data, obtained through validation sheets completed by material experts, language experts, and media experts, as well as questionnaires measuring the responses of teachers and students toward the developed learning media.The results of the practicality test indicate that the Canva-based learning media achieved a score of above 90%, categorized as highly practical. This demonstrates that the media is easy to use, practical, and effective in increasing students’ interest in learning during the instructional process. Therefore, it can be concluded that the development of Canva-based learning media for fourth-grade elementary school mathematics is valid and practical for use in teaching and learning activities.